1992
DOI: 10.2165/00003495-199244050-00009
|View full text |Cite
|
Sign up to set email alerts
|

Bepridil

Abstract: Bepridil is a calcium antagonist with direct negative chronotropic, dromotropic, inotropic and vasodilatory actions which reduces myocardial oxygen consumption and increases coronary blood flow, leading to a significant anti-ischaemic and antianginal effect in the absence of reflex tachycardia. In contrast to other calcium channel blockers, bepridil produces only modest peripheral vasodilatation and displays weak antihypertensive activity. Its plasma elimination half-life of 1 to 2 days permits once daily admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The original GE-HTS screen also led to the identification of the FDA-approved ion flux Ca 2+ modulator, bepridil, a class IV antiarrhythmic drug [ 191 ] with limited toxic effects. This observation was leveraged to challenge a repurposing effort in NOTCH1 mutated cancers.…”
Section: Targeting Notch Traffickingmentioning
confidence: 99%
“…The original GE-HTS screen also led to the identification of the FDA-approved ion flux Ca 2+ modulator, bepridil, a class IV antiarrhythmic drug [ 191 ] with limited toxic effects. This observation was leveraged to challenge a repurposing effort in NOTCH1 mutated cancers.…”
Section: Targeting Notch Traffickingmentioning
confidence: 99%
“…Bepridil helps to decrease the frequency of angina attacks, as measured by the use of nitrates. However, concerns regarding prolongation of the corrected QT interval and torsade de pointes have limited its use in North America [45]. …”
Section: Second-generation Anti-anginal Drugsmentioning
confidence: 99%
“…As with the entire spectrum of coronary disease, optimal medical therapy and risk factor modification provides important prognostic and symptomatic benefit in these patients. A wide array of pharmacological armamentarium is now available to manage the patients with chronic stable angina as outlined in Table 1 [27, 3136, 3840, 42, 43, 45, 50, 51, 53, 54, 67, 72, 78, 80, 8284, 8792, 95, 97, 102, 107, 132144]. …”
Section: Expert Opinionmentioning
confidence: 99%
“…Bepridil is known as a calcium channel blocker, possessing a distinct electrophysiological profile [7,8]. It is widely utilized as a therapeutic agent for cardiovascular disorders, known for its ability to decrease myocardial oxygen consumption and enhance coronary blood flow [9]. The equilibrium column-binding technique revealed that bepridil exhibits specific binding affinity towards calmodulin-an intracellular calcium receptor protein-in Life 2023, 13, 1607 2 of 12 the presence of calcium ions.…”
Section: Introductionmentioning
confidence: 99%